(untitled) (Proceeding of SINERGY, 2026)
This study examines the role of financing in Islamic banking, focusing on Bank Tabungan Negara Syariah’s financial intermediation function amid dynamic economic conditions during 2015–2024. The main issue in this study is the volatility of financing, driven by micro- and macroeconomic factors, particularly interest rates, inflation, the financing-to-third-party funds ratio, and third-party funds. The objectives of this study are to analyze the Influence of these four variables on Bank Tabungan Negara Syariah financing and to predict financing trends in the coming period. This study adopts a quantitative approach, utilizing multiple linear regression to empirically examine the effect of predictor variables on financing outcomes and an autoregressive integrated moving average (ARIMA) model to predict financing trends. The novelty of this study lies in combining causal relationship analysis and financing trend forecasting within a single research framework, which has not been widely applied to Bank Tabungan Negara Syariah. The findings indicate that financing declines significantly as interest rates increase, while inflation exhibits a weak and statistically non-meaningful inverse association. In contrast, both the financing ratio and third-party funds demonstrate a strong and positive contribution to financing levels. The forecasting results indicate that the financing trend is projected to increase over the projection period. The conclusion of this study confirms that a combination of internal and external factors of the bank influences financing performance. Further research is recommended to add other variables and use alternative forecasting methods to obtain more comprehensive results.